Four Types of RNA Modification Writer-Related lncRNAs Are Effective Predictors of Prognosis and Immunotherapy Response in Serous Ovarian Carcinoma - Ye, Lele; Pan, Kan; Fang, Su; Wu, Su-Ni; Chen, Su; Tang, Sangsang; Wang, Nan; Zhang, Haoke; Tong, Xinya; Shi, Xinyu; Feng, Shiyu; Xiang, Dan; et al. (Frontiers in Immunology, 2022)
Serous ovarian carcinoma (SOC) is a gynecological malignancy with high mortality rates. Currently, there is a lack of reliable biomarkers for accurate SOC patient prognosis. Herein, we analyzed SOC data from The Cancer Genome Atlas (TCGA) to identify prognostic biomarkers. Through Pearson correlation analysis, univariate Cox regression analysis, and LASSO-penalized Cox regression analysis, we identified nine lncRNAs significantly associated with four types of RNA modification writers (m6A, m1A, APA, and A-I) as well as with the prognosis of SOC patients (P < 0.05). Six writer-related lncRNAs were ultimately selected following multivariate Cox analysis. We established a risk prediction model based on these six lncRNAs and evaluated its prognostic value in multiple groups (training set, testing set, and entire set). Our risk prediction model could effectively predict the prognosis of SOC patients with different clinical characteristics as well as their responses to immunotherapy. Lastly, we validated the predictive reliability and sensitivity of the lncRNA-based model via a nomogram. The present study explored the association between RNA modification writer-related lncRNAs and SOC prognosis, providing a potential complement for the clinical management of SOC.